Dispersion of seeds at night and day in sub-Andean forests, Cueva Los Guacharos Park, Colombia - Bautista Plazas, Sebastián (2023)
Introduction: Much has been argued about the importance of the role that different types of frugivores play as seed dispersers in plant communities, but few studies have been actually carried out. Objective: We evaluated and compared diurnal and nocturnal seed dispersal in a primary and secondary sub-Andean forest in Southern Colombia. Methods: We estimated number and biomass (kg/ha) of seeds dispersed over one year (2017) using 60 fruit traps that were checked before sunrise and before sunset for 10 continuous days every two months. Results: We found that from 1 874 dispersed seeds, 55.8 % (10.9 kg/ha) were collected during the day and 44.2 % (6.39 kg/ha) at night. There were no significant differences between diurnal and nocturnal seed dispersal in number of seeds or biomass. We also found no difference in between seed dispersal that in the primary forest and secondary forest over time. Within diurnal organisms, primates and fruit-eating birds appear to be primarily responsible for this ecosystem service during the day; while bats, birds (e.g. oilbirds), and probably primates did so during the night. Conclusions: Diurnal and nocturnal dispersal seem to be equal in terms of number and weight of seeds, but not in the similarity of dispersed plant species. It remains a challenge to recognize the relative importance of different fruit-eating organisms as seed dispersers using fruit trap methods.